1992
DOI: 10.1002/art.1780350912
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction in Sjögren's syndrome T cells. Abnormalities associated with a newly described human A‐type retrovirus

Abstract: Objective. To study the effects of a novel A-type retrovirus, detected in cocultures of lip biopsy specimens from Sjogren's syndrome (SS) patients and a human T cell line, on the infected T cells.Methods. Interleukin-2 (IL-2) and IL-6 secretion were measured by bioassay and enzyme-linked immunosorbent assay, respectively, in the infected and noninfected cell lines. Surface antigen expression was determined by flow cytometry, using monoclonal antibodies. Protein kinase C (PKC) activity was measured using an enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…A link between Ca2+ influx, phospholipid hydrolysis and polyamines has been reported by us and other investigators [27,[34][35][36][37]. We found that polyamines inhibited Ca2+ influx in Balb/c splenic T-cells in a cell-specific manner [27], the CD4 subset being more susceptible to the inhibitory effect of polyamines than the CD8 subset.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A link between Ca2+ influx, phospholipid hydrolysis and polyamines has been reported by us and other investigators [27,[34][35][36][37]. We found that polyamines inhibited Ca2+ influx in Balb/c splenic T-cells in a cell-specific manner [27], the CD4 subset being more susceptible to the inhibitory effect of polyamines than the CD8 subset.…”
Section: Discussionsupporting
confidence: 79%
“…Polyamine-mediated inhibition of the phospholipid-sensitive Ca2+-dependent protein kinase C has also been reported [35]. It is possible that the effect of polyamines might be exerted through their oxidation products [36]. Furthermore, polyamines may react with biological membranes and induce a variety of effects including the promotion of membrane fusion and inhibition of the association of protein kinases with the membranes [37].…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary report by Flescher et al (1991) showed that anti-CD-3-induced intracellular Ca2+ mobilization in normal human peripheral lymophocytes was suppressed by spermidine. They also found significantly decreased Ca2+ influx in T-cells of rheumatoid-arthritis patients that contained constitutively higher levels of polyamines than that of normal lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The genome encoding HIAP-I has not been characterized; however, cells expressing these RVLPs are reported to have reduced protein kinase C activation and IL-2 production and to express reduced levels of CD4 and increased levels of MHC class II in comparison to normal H9 cells (143). In addition, stimulation of the same cells with phorbol myristate acetate resulted in an increased production of RVLPs, although these RVLPs appeared as cytoplasmic clusters of particles of smaller diameter (approximately 33 nm) (112) and are therefore unlikely to be the same particles observed originally.…”
Section: Human Intracisternal A-type Particlesmentioning
confidence: 99%